Consuming Jesus: beyond race and class divisions in a consumer church - Metzger, Paul Louis (William B. Eerdmans Publ., 2007)
A faulty order : retreating battle camps and homogeneous units -- Disordered vision : battling the consumer balrog -- Reordering the cosmic powers : turning tables at the stone table -- Reordering the Christian's life : the supernatural shakeup -- Reordering the church : recovering the lost ark -- Reordering the church's outreach : overcoming market -- Forces and building beloved community